Acute respiratory distress syndrome in a case of Plasmodium vivax malaria - Malik, Atiullah; Ponvijaya, Yadav; Sajjan, Kshithija; Gurbani, Chirag (International Journal Of Community Medicine And Public Health, 2021)
Acute respiratory distress syndrome (ARDS) is a life threatening complication of many infectious diseases like malaria, H1N1, bacterial pneumonia, and leptospira. Malaria is an important treatable cause of ARDS. ARDS can develop either at initial presentation or after initiation of treatment when the parasitaemia is falling and patient is improving. 58 year old female presented with high grade fever and breathlessness since 5 days. Arterial blood gas (ABG) on admission showed type 1 respiratory failure and chest X-ray was suggestive of ARDS. Thus patient was shifted to intensive care unit and was put on non-invasive ventilation. PBS was positive for Plasmodium vivax malaria and patient was started on antimalarial drugs. Considering the epidemic of H1N1 swab was sent for polymerase chain reaction (PCR) which turned out to be negative. Thus antimalarial and supportive treatment for ARDS was continued. Patient was discharged on day 11 and started on tablet primaquine to prevent relapse. ARDS is a hard to predict late complication of severe malaria. ARDS in malaria is a disease with high mortality. Early diagnosis and institution of specific antimalarial treatment along with assisted ventilation can be life-saving.